2013
DOI: 10.1002/iub.1231
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-7 upregulates Cullin 5 (CUL5) to facilitate G1/S transition in human hepatocellular carcinoma cells

Abstract: MicroRNAs (miRNAs) are small, non-coding RNAs that participate in the regulation of gene expression. In this study, we demonstrate that miR-7 was downregulated in hepatocellular carcinoma (HCC) tissues compared to adjacent non-tumor tissue. Over-expression of miR-7 in QGY-7703 and HepG2 cell lines inhibited colony formation and induced G1/S phase arrest, whereas knockdown of miR-7 produced the opposite phenotype. A tumor suppressor gene, CUL5, was identified as a direct target of miR-7, and CUL-5 is upregulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 19 publications
2
35
0
Order By: Relevance
“…Accompanying these deficiencies, SENP8 knockout cells also showed aberrant G1/S cell cycle progression and accelerated cell growth (Figure 6). Interestingly, these cell cycle alterations partially phenocopy previously reported defects associated with the loss of either Cul1 (Dealy et al, 1999; Wang et al, 1999; Chen and Li, 2010) or Cul5 function (Burnatowska-Hledin et al, 2001; Buchwalter et al, 2008; Bradley et al, 2010; Ma et al, 2013a; Willis et al, 2017). Through an unbiased proteomic screen in which we enriched for K-ε-GG remnant-containing peptides in MG132-treated cells, we were able to identify several candidate substrates with deregulated ubiquitylation status and stability in the SENP8 knockout cells that could potentially contribute to G1/S progression defects.…”
Section: Discussionsupporting
confidence: 71%
“…Accompanying these deficiencies, SENP8 knockout cells also showed aberrant G1/S cell cycle progression and accelerated cell growth (Figure 6). Interestingly, these cell cycle alterations partially phenocopy previously reported defects associated with the loss of either Cul1 (Dealy et al, 1999; Wang et al, 1999; Chen and Li, 2010) or Cul5 function (Burnatowska-Hledin et al, 2001; Buchwalter et al, 2008; Bradley et al, 2010; Ma et al, 2013a; Willis et al, 2017). Through an unbiased proteomic screen in which we enriched for K-ε-GG remnant-containing peptides in MG132-treated cells, we were able to identify several candidate substrates with deregulated ubiquitylation status and stability in the SENP8 knockout cells that could potentially contribute to G1/S progression defects.…”
Section: Discussionsupporting
confidence: 71%
“…In addition, miR-7 binds at the 3 0 UTR of CUL5, inhibiting colony formation and inducing G1/S phase arrest. 50 Further study found that miR-7 directly targets phosphoinositide 3-kinase catalytic subunit delta (PIK3CD) and 2 novel, putative genes: mTOR and p70S6K. As a result, PIK3CD, the mammalian target of rapamycin (mTOR) and p70S6K, are all repressed by miR-7 overexpression.…”
Section: Roles Of Circrnas In the Oncogenesis And The Malignant Behavmentioning
confidence: 99%
“…Another two studies reported that miR-7 was expressed at a high level during human pancreatic islet development [10,17] . For malignancy, it has been demonstrated that miR-7 is downregulated in cancer tissue of digestive malignancies such as GC [18][19][20] , CRC [21,22] and hepatocellular carcinoma (HCC) [23] by comparison with normal tissues, suggesting that it acts as a suppressor. A similar conclusion was drawn in a study of hydroxycamptothecin-resistant GC cells [24] .…”
Section: Expression Of Mir-7mentioning
confidence: 99%
“…MiR-7 regulates the PI3K/Akt/mammalian target of rapamycin in vitro and in vivo, which functions downstream of EGFR, suggesting that miR-7 is a potential target for treating or diagnosing/prognosing HCC [28] . Likewise, ectopic expression of cullin 5, a novel target gene of miR-7, inhibits HCC cell proliferation, arrests cell cycle progression, and suppresses colony formation, although the exact pathway remains unclear [23] . Moreover, which miR-7 targeted SET domain containing 8 leading to increased p53 expression and decreased Bcl-2 level, curcumin suppressed cell growth, migration and invasion, and induced apoptosis in PC cells, indicating that targeting miR-7 is a useful therapeutic option for PC [33] .…”
Section: Hccmentioning
confidence: 99%